Antisocial Personality Disorder of The Main Character in The Bad Seed Movie - Ika Veronika . (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2017)
The Bad Seed movie tells the story of Emma, a little girl who has above-average intelligence, but her father, David, realizes that her 9-year-old daughter has a personality disorder. Her father found out her daughter, Emma has no empathy for fellow humans and even without hesitation kills other people who make her angry. This study intended to show antisocial personality disorder as reflected of Emma in The Bad Seed movie, directed by Rob Lowe. This study applies the theory of personality disorders by Theodore Millon. This research uses descriptive qualitative research. Data collection was carried out through four steps, such as watching, screenshots, note-taking, and identifying data. The results of this study indicate that the main character has antisocial personality disorder. The main character in The Bad Seed movie, shows five criteria for antisocial personality disorder is: swindler or liar, manipulative, aggressive and irritable, impulsive, and lack of empathy and lack of remorse.While the variant of antisocial personality disorder is reflected in the main character, namely the pure variant or the jealousy/envy.